Pengaruh Kehidupan Sosial Dan Ekonomi Keluarga Terhadap Pernikahan Dini Pada Tahun 2020 - Danang Prio Utomo; Rini Aprianti; Muhamad Ali (Universitas Hamzanwadi, 2020)
West Nusa Tenggara (NTB) is recorded as a province with a fairly high rate of young marriage (merariq kodek), especially in East Lombok then North Lombok. Many factors cause underage marriages, including factors due to love, economic factors, matchmaking factors, dropping out of school, and pregnancy outside of marriage. The purpose of this study was to examine the influence of family social and economic life on early marriage. The method used is a quantitative method with a descriptive approach, in general there are 33 samples (respondents) but after using the sample calculation technique with the Slovin formula, 30 respondents can be drawn, the respondents consist of various backgrounds of married age, different occupations. All data were processed by multiple regression analysis by looking at the validity test, reliability, classical assumption test (data normality test, multicollinearity test, and heteroscedasticity test) and hypothesis testing using the F test and t test.The results of this study indicate that there is an influence of family social and economic life on early marriage. This is indicated by the simultaneous test results of F count of Early Marriage at (45.191) with a probability level (0.000) which means that together the Social and Economic Life of the Family has a share in influencing Early Marriage in the hamlets of Penyenggir, Manggong and Batu Gapit. 3) From the significant test it is also proven that each independent variable also has a significant effect on the dependent variable. Social life variable (X1) has a significant influence on early marriage in the villages of Penyenggir, Manggong and Batu Gapit. This is indicated by t count (4.537) with p value (sig) 0.000 smaller than 0.05, meaning that social life has a role in influencing early marriage in the village of West Sikur. The family economic variable (X2) also has a significant effect on early marriage in the village of West Sikur. This is indicated by t count (3.735) with a p value (sig) of 0.001, which is below 0.05, which means that the family economy has a role in influencing early marriage in the hamlets of Penyenggir, Manggong and Batu Gapit.